THE PALESTINO-ISRAELIAN TRACK: THE FAILURE OF OBAMA ADMINISTRATION’S MIDDLE EAST POLICY - A. V. Krylov; V. M. Morozov (Vestnik MGIMO-Universiteta, 2017)
The article examines the attempts of American diplomacy to achieve a breakthrough on the Palestinian-Israeli track between July 29, 2013 and April 24, 2014 in order to come close to signing the Permanent Status Agreement between the conflicting parties under the US mediation within the framework of the previous agreements reached at the tripartite Summit of 2000 in Camp David. The study is based on an analysis of the “Kerry Plan” prepared by the US State Department, which laid the foundations of solving key issues of the PalestinianIsraeli confrontation. Details of the Kerry Plan were never disclosed, but its content was reconstructed by the authors on the basis of an analysis of the materials of the negotiations that were conducted under the auspices of the United States in the past. The article draws a parallel between the negotiation process in 2013-2014 and the process that was initiated by the administration of President B. Clinton in 2000-2001. The plan proposed by J. Kerry, like the initiative of B. Clinton, was focused on solving only the issue of future borders by exchanging territories, but did not touch upon other principal issues of the Permanent Status (refugees, Israeli settlements, the status of Jerusalem). It is obvious that such an approach, which completely disavowed the existing international legal basis for the Middle East settlement, was leaning to deliberate failure. The study allows to conclude that the settlement of the conflict under the auspices of the United States on a separate basis under the “Camp David scheme”, successfully approved by the US diplomacy in resolving disputable issues between Egypt and Israel in the late 1970s, does not work on the Palestinian track.